2005
DOI: 10.1017/s0001867800000392
|View full text |Cite
|
Sign up to set email alerts
|

Perfect simulation of Hawkes processes

Abstract: Our objective is to construct a perfect simulation algorithm for unmarked and marked Hawkes processes. The usual straightforward simulation algorithm suffers from edge effects, whereas our perfect simulation algorithm does not. By viewing Hawkes processes as Poisson cluster processes and using their branching and conditional independence structures, useful approximations of the distribution function for the length of a cluster are derived. This is used to construct upper and lower processes for the perfect sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
82
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 27 publications
0
82
0
Order By: Relevance
“…Taking expectation on both side, and setting λ = Eλ t , we get the equation λ = µ + cλ , and the necessary (and sufficient, see [11]) condition for the existence of a Hawkes process satisfying (2):…”
Section: Modeling Single-unit Activity Via Hawkes Processesmentioning
confidence: 99%
“…Taking expectation on both side, and setting λ = Eλ t , we get the equation λ = µ + cλ , and the necessary (and sufficient, see [11]) condition for the existence of a Hawkes process satisfying (2):…”
Section: Modeling Single-unit Activity Via Hawkes Processesmentioning
confidence: 99%
“…Note also that simulation algorithms of Hawkes processes are easily available (see e.g. Ogata, 1981;Moller and Rasmussen, 2005, and Appendix A), allowing further developments for the use of the estimated models. These practical properties make Hawkes processes good candidates for the study of the clustering of events empirically observed in order book models (Hautsch, 2004;Bowsher, 2007;Large, 2007;Bacry et al, 2012).…”
Section: Testing the Calibrationmentioning
confidence: 99%
“…Taking a different point of view, a more recent work by Moller and Rasmussen (2005) claims to provide better quality simulations, without edge effects. In this appendix however, we describe the simple thinning algorithm in a multidimensional setting, because of its intuitive progression and its ability to be straightforwardly generalized to any point process described with its conditional intensity.…”
mentioning
confidence: 99%
“…As there is an intensity-based as well as cluster-based definition, there exist various simulation and estimation techniques which take advantage of either perspective on Hawkes processes. To mention a few, for simulation we have the thinning approach (Ogata 1981), the timechange approach based on the random time-change theorem (Meyer 1971) and applied specifically to Hawkes processes for instance in (Ozaki 1979), exact simulation (Dassios and Zhao 2013) and perfect simulation (Møller and Rasmussen 2005). Concerning estimation techniques, the standard maximum likelihood approach can for example be found in Ozaki (1979).…”
Section: Introductionmentioning
confidence: 99%